Three squat lobsters (Crustacea: Decapoda: Anomura) from tropical West Pacific seamounts, with description of a new species of Uroptychus Henderson, 1888 - Dong, Dong; Li, Xinzheng; Lu, Bo; Wang, Chunsheng (Zootaxa, 2017)
Three species of squat lobster, Uroptychus inaequipes n. sp., Munidopsis bairdii (Smith, 1884), and M. kensmithii Jones & Macpherson, 2007, are reported from the seamounts of the tropical West Pacific. The new species of Uroptychus is distinguished from its congeners by having short antennal scales, and non-produced anterolateral corners of thoracic sternite 4. Munidopsis kensmithii is recorded from the West Pacific for the first time.